2022
DOI: 10.1186/s13287-022-03093-7
|View full text |Cite
|
Sign up to set email alerts
|

Circular RNA BIRC6 depletion promotes osteogenic differentiation of periodontal ligament stem cells via the miR-543/PTEN/PI3K/AKT/mTOR signaling pathway in the inflammatory microenvironment

Abstract: Background Periodontal ligament stem cells (PDLSCs) are the ideal seed cells for periodontal tissue regeneration. It is well established that persistent inflammation significantly impairs the osteogenic differentiation capability of PDLSCs. Therefore, maintaining PDLSC osteogenic potential under the inflammatory microenvironment is important for treating bone loss in periodontitis. The aim of our study was to explore the potential role of circular RNA BIRC6 (circBIRC6) in regulating osteogenic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 24 publications
(29 reference statements)
1
18
0
Order By: Relevance
“…This conclusion is similar to that of the study by Lei et al on pancreatic acinar cells (Kong et al, 2019). However, some studies have suggested that PTEN is a protective factor against inflammation and ABL (Fu et al, 2019;Zhao et al, 2022) separately (Lee et al, 2018;Wei et al, 2020). However, Cao et al found that TNF-α expression was downregulated in PTEN −/− macrophages treated with LPS and concluded that PTEN is a negative regulator of Fc gamma receptors (FcγR) signaling, while a positive regulator of TLR4 signaling in the macrophage inflammatory response (Cao et al, 2004).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This conclusion is similar to that of the study by Lei et al on pancreatic acinar cells (Kong et al, 2019). However, some studies have suggested that PTEN is a protective factor against inflammation and ABL (Fu et al, 2019;Zhao et al, 2022) separately (Lee et al, 2018;Wei et al, 2020). However, Cao et al found that TNF-α expression was downregulated in PTEN −/− macrophages treated with LPS and concluded that PTEN is a negative regulator of Fc gamma receptors (FcγR) signaling, while a positive regulator of TLR4 signaling in the macrophage inflammatory response (Cao et al, 2004).…”
Section: Discussionsupporting
confidence: 91%
“…on pancreatic acinar cells (Kong et al., 2019). However, some studies have suggested that PTEN is a protective factor against inflammation and ABL (Fu et al., 2019; Zhao et al., 2022). A possible reason for this contradiction could be the dual role of PTEN in the macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…hDPSCs and hPDLSCs were isolated and cultured as previously described by the group. [46,47] Patients and Clinical Samples: The research protocol for reusing clinical specimens and medical information was approved by the Ethics Committee of the First Affiliated Hospital of Sun Yat-sen University (IRB Number: 2022-056), and all procedures adhered to the Declaration of Helsinki guidelines. Written informed consent was obtained from all subjects.…”
Section: Methodsmentioning
confidence: 99%
“…47 However, the circBIRC6/miR-543 axis regulates the osteogenic differentiation of PDLSCs through the PTEN/PI3K/AKT/mTOR signaling pathway, and silencing PTEN promotes the osteogenic differentiation of PDLSCs. 48 Moreover, when PTEN expression was decreased, PDLC apoptosis decreased, and cell proliferation was promoted. 49 The role of PTEN in periodontitis with diabetes has not been reported.…”
Section: Discussionmentioning
confidence: 99%
“…PTEN expression was reported to be reduced in a mouse model of periodontitis, and its deficiency activates IL‐1β and TNF‐α, which increases the number of osteoclasts and leads to alveolar bone loss 47 . However, the circBIRC6/miR‐543 axis regulates the osteogenic differentiation of PDLSCs through the PTEN/PI3K/AKT/mTOR signaling pathway, and silencing PTEN promotes the osteogenic differentiation of PDLSCs 48 . Moreover, when PTEN expression was decreased, PDLC apoptosis decreased, and cell proliferation was promoted 49 .…”
Section: Discussionmentioning
confidence: 99%